PENGARUH KUALITAS PRODUK DAN PENETAPAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOBIL NISSAN ALL NEW LIVINA PADA CABANG INDOMOBIL NISSAN SM AMIN PEKANBARU - Putri Maria Febriani. S; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research was conducted at the Indomobil Nissan SM Amin Pekanbaru Branch located on Jl. SM Amin, Labuh Baru, Kec. Umbrella Sekaki, Pekanbaru, Riau. The purpose of this study was to determine the effect of product quality and pricing on purchasing decisions for the Nissan All New Livina at the Indomobil Nissan SM Amin Pekanbaru branch partially and simultaneously. In this research, the method used is descriptive quantitative analysis with SPSS program. The population in this study were all consumers who purchased the Nissan All New Livina at the Indomobil Nissan SM Amin Pekanbaru Branch in the last year, 2020, as many as 54 respondents. To determine the sample using the accidental sampling method. Data collection techniques through questionnaires and interviews, types and sources of data using primary data and secondary data, measurement collection techniques using a Likert scale. From data analysis which includes validity test, reliability test, simple linear regression analysis, multiple linear analysis, determination analysis and significance test with t test (partial) test, and f test (simultaneous). The results of this study indicate that the results of the first t test hypothesis testing, product quality on purchasing decisions, namely t count (3,881) > t table (1,6746) meaning that product quality has a significant effect on purchasing decisions. Second, pricing on purchasing decisions is t count (3.606) > t table (1.6746) meaning that product quality has a significant effect on purchasing decisions. The results of the f test product quality and pricing have a significant effect on purchasing decisions, namely f count (10.263) > table (3.18). This means that product quality and pricing simultaneously have a significant effect on purchasing decisions at the Indomobil Nissan SM Amin branch in Pekanbaru. Keywords: Product Quality, Pricing, Purchase Decision